Situation Report: Romania, 5 June 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Literary Journal Counters Soviet Attack Problems of the Romanian Theater High-Level Visitors Discuss Romanian- Bulgarian Economic Relations Draganescu Discusses Economic Co-operation in Yugoslavia Romanian-Ecuadorian Co-operation in Oil Industry Allon Visits Romania Substantial Increase in Romanian-Italian Trade in 1974 State Council Decree Reflects Ideological Concern for Youth